2021
DOI: 10.1007/s10694-021-01122-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Micro-Scale and Solid Material Data for Modelling Heat Transfer in Stone Wool Composites Under Heat Exposures

Abstract: Modelling capabilities have drastically improved in the last decade. However, in most of the cases the fire response of building elements is predicted by fitting input material properties to the models in order to match test data. This paper presents models developed to predict the unexposed side temperature of stone wool layered composites with stainless steel or gypsum claddings exposed to severe heat conditions. The suitability of material thermal properties from literature and reaction kinetic parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…The authors reported two exothermic peaks and attributed them to the burning of the binder and crystallization of the amorphous material. The thermal behavior of mineral wool was investigated and modelled in [11,12]. In [11], a multiphysics model of heat and mass transfer coupled with the chemical decomposition of the organic content was developed while in [12] models for predicting the temperature of the unexposed side of sandwich composites made of mineral wool with a stainless steel or plasterboard cladding were presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors reported two exothermic peaks and attributed them to the burning of the binder and crystallization of the amorphous material. The thermal behavior of mineral wool was investigated and modelled in [11,12]. In [11], a multiphysics model of heat and mass transfer coupled with the chemical decomposition of the organic content was developed while in [12] models for predicting the temperature of the unexposed side of sandwich composites made of mineral wool with a stainless steel or plasterboard cladding were presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Genellikle yangınların sonraki aşamalarında yapının deformasyonları, alçı levhaların çatlaması ve düşmesi göçme sürelerini belirlemektedir [15]. Sayısal çalışmaların çoğu, esas olarak GPB'nin termal davranışına odaklanmakla [16][17][18] birlikte, GPB'nin yüksek sıcaklıklarda mekanik özellikleri hakkında yalnızca sınırlı sayıda çalışma vardır [19][20][21]. Alçıdan imal edilen iki tarafı kağıtla kaplı olan alçıpanların bir çeşidi olan kırmızı alçıpan yangına karşı dayanım istenen yerlerde kullanılmaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified